Penguatan Kemampuan Bertutur Dan Literasi Melalui Story Telling Cerita Rakyat Danau Toba Di Desa Kota Tanah - Indah Sulmayanti; Lailatul Fitria; suyanti; Lutfi Miftakhurohmah (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program titled Strengthening Speaking and Literacy Skills through Storytelling of the Legend of Lake Toba in Kota Tanah Village was implemented to address the issue of low basic literacy skills among children, particularly in reading comprehension and speaking abilities. Initial observations revealed weaknesses in understanding reading materials and conveying information orally. As a solution, the service team conducted a storytelling program using an interactive approach. The results of the activity showed significant improvement in several aspects. Students who could speak fluently, expressively, with clear intonation, demonstrated deep understanding of the story, and showed high confidence received scores ranging from 90–100 (excellent). Students who spoke fairly fluently and expressively, understood the story, and showed enthusiasm during the storytelling activity received scores between 80–89 (good). Students who were able to tell stories with proper structure but still showed hesitation or minor errors in vocabulary and pronunciation received scores between 70–79 (fair). Students who lacked confidence, often paused while telling stories, and had limited understanding of the story received scores between 60–69 (poor). Meanwhile, students who could not tell stories clearly, did not understand the story content, and showed insufficient effort received scores below 60 (very poor).